Variation of anthocyanins and other major phenolic compounds throughout the ripening of four Portuguese blueberry (Vaccinium corymbosum L) cultivars - Silva, Sara (2017)
Blueberries are widely recognised as one of the richest sources of bioactive compounds, among which are anthocyanins, though the ripeness of berries has been reported as affecting the phytochemical composition of fruits. Therefore, the present work aimed to evaluate the variation of anthocyanins, and other major phenolics, throughout five ripening stages in four blueberry cultivars. The results showed that the antioxidant capacity and anthocyanin content increased during ripening, reaching the highest values when the blueberries are collected from bunches comprised of 75% ripe blueberries. Antagonistically, the amount of phenolic acid decreases, while the quercetin-3-glucoside levels remain stable. Furthermore, Goldtraube blueberries appear to possess, systematically, higher amounts of phenolic compounds than the other cultivars studied. Thus, when seeking the highest yield of anthocyanins, the preferred harvest should occur in bunches that contain ca 75% of ripe blueberries and, considering the cultivars assayed, the Goldtraube cultivar appears to bethe richest in phenolic compounds.